Perception of Environmental Impacts of Wind Farms in Agricultural Areas of Northeast Brazil - Manoel Fortunato Sobrinho Junior; Maria Carolina Ramirez Hernandez; Sthenia Santos Albano Amora; Elis Regina Costa de Morais (Energies, 2021)
In recent years, wind power in Brazil has emerged as an alternative to diversify the country′s energy mix and minimize the emission of pollutants derived from fossil fuels. The state of Rio Grande do Norte, in the Brazilian Northeast, has considerable potential for the generation of wind energy due to the occurrence of strong winds in many areas along the coast and in the interior of the state, in places with higher altitudes. However, wind energy, despite being considered clean and renewable, can cause environmental impacts in those places. Thus, the present study analyzed the perception of environmental impacts caused by the installation of wind farms in the agricultural areas of Northeast Brazil. The study was carried out in the municipality of Serra do Mel, in the western region of the state of Rio Grande do Norte, based on a survey of local farmers. The study concluded that farmers live without major problems and without apparent conflicts with wind farms but have little knowledge about the environmental impacts. In the perception of most farmers, there are few negative environmental impacts, and those that exist are barely noticed or still do not cause damage to most farmers in the region.